Psychic distress and special educational needs of unaccompanied minors (UM). Stories and educational perspectives in a multiple case study - Andrea Traverso; Eleana Marullo (Educazione Interculturale, 2020)
Although the decrease of UM in Italy, psychological and psychiatric problems show deep discomforts that manifest themselves within the services (educational and scholastic) in a violent way (in behaviour, relationship, inter-personal and intra-personal communication).  The UMs arrive in Europe after a long and dangerous journey, carrying a heavy baggage, made of traumatic experiences that before and during their journey have settled on body and mind.  That baggage can be even more burdensome from the experience they live after their arrival, in a foreign country without reference points and with the feeling of a progressive departure from home. The article explores the dimensions and manifestations of trauma in UMs, in particular Post-Traumatic Stress Disorder and Dissociative Syndrome. The contribution concludes with the presentation of a research conducted as a multiple case study, useful to discuss the relapses in inclusion processes; the effectiveness of educational interventions and the building of relationships based on trust and recognition of human solidarity.